Evidence-Based Practice Through the Lens of Pediatric Occupational Therapy Clinic Managers in the Philippines - Leosala, Louise Odeth (Technium Social Sciences Journal, 2023)
The implementation of evidence-based practice (EBP) involves a systematic approach that plays a critical role in healthcare service delivery. In a world of innovations in the health sciences, keeping up with the advances through evidence-based practice is vital for allied healthcare professionals such as Occupational Therapists. This phenomenological study focused on exploring the realities of the supports, barriers, and strategies in EBP implementation as experienced by occupational therapy (OT) clinic managers. A semi-structured interview was utilized to gather data from five managers in selected pediatric OT clinics in the Philippines. Interviews were transcribed and data were analyzed using Moustakas’ phenomenological analysis which resulted in 7 major themes (a) Value of Evidence-based Practice, (b) Organizational Supports, (c) Organizational Barriers, (d) Structure Creation, (e) Skills Building, (f) System for Rewards, and (g) Seeking Resources which were categorized into textural and structural descriptions of the phenomenon. This study concluded that OT managers shared a common pattern of experiences on EBP value, organizational management supports and barriers. OT clinic managers also addressed barriers by utilizing strategies to improve EBP practice and healthcare service delivery.